Nitrate acts at the Arabidopsis thaliana shoot apical meristem to regulate flowering time - Olas, Justyna Jadwiga (New Phytol, 2019)
Optimal timing of flowering, a major determinant for crop productivity, is controlled by environmental and endogenous cues. Nutrients are known to modify flowering time; however, our understanding of how nutrients interact with the known pathways, especially at the shoot apical meristem (SAM), is still incomplete. Given the negative side‐effects of nitrogen fertilization, it is essential to understand its mode of action for sustainable crop production. We investigated how a moderate restriction by nitrate is integrated into the flowering network at the SAM, to which plants can adapt without stress symptoms. This condition delays flowering by decreasing expression of SUPRESSOR OF OVEREXPRESSION OF CONSTANS 1 (SOC1) at the SAM. Measurements of nitrate and the responses of nitrate‐responsive genes suggest that nitrate functions as a signal at the SAM. The transcription factors NIN‐LIKE PROTEIN 7 (NLP7) and NLP6, which act as master regulators of nitrate signaling by binding to nitrate‐responsive elements (NREs), are expressed at the SAM and flowering is delayed in single and double mutants. Two upstream regulators of SOC1 (SQUAMOSA PROMOTER BINDING PROTEIN‐LIKE3 (SPL3) and SPL5) contain functional NREs in their promoters. Our results point at a tissue‐specific, nitrate‐mediated flowering time control in Arabidopsis thaliana.